Peculiarities of the Motor Activity Organization of Students - Kholova, Shakhnoza Mardonovna (International Journal of Psychosocial Rehabilitation, 2020)
A continuously increasing flow of information and an increase in the volume of theoretical disciplines studied in higher educational institutions narrows the range of motor activity of students. In this regard, the organization and management of motor activity of those involved in the school day, semester and throughout the entire period of study at the university becomes more and more urgent. Mental ability and student health largely depend on the optimization of motor activity and the management of the process of its implementation. Under the influence of an intense sedentary lifestyle in the human body, typical, regularly repeating changes occur, which, as a rule, indicates fatigue, deterioration number of physiological functions of the body. They lead to imbalance, processes of excitation and inhibition in the central nervous system, resulting reduced mental work capacity. In order to ensure high human workability in conditions of limited mobility, the functional state of the motor analyzer plays an important role. It is known that its activity creates a favorable background for the work of all systems of the human body. Inadequate motor activity and lack of muscle tension during work reduce the functional capabilities of the body as a whole and adversely affect a person’s working ability. At the same time, the activity of the cardiovascular and respiratory systems worsens, attention and memory decrease. To eliminate subjective factors of fatigue and increase to some extent the person’s working ability by increasing physical activity, by introducing physical exercises.